Relasi Manusia dan Alam dalam Kesenian Talempong Kayu Masyarakat Nagari Rangking Luluih Kabupaten Solok - Septriani, Septriani; Satria, Edi (Asosiasi Ide Bahasa Kepri, 2024)
This study examines the relationship between humans and nature in the art of wooden talempong in Nagari Rangking Luluih, Solok Regency. Humans and nature are two inseparable entities. The natural environment determines human culture. Likewise, humans can change the natural environment in their efforts to adapt and utilize resources. Art is one of the universal elements of culture whose creation can also come from nature. One example is the wooden talempong. Therefore, the problem raised in this study is how the background of the creation and repertoire in wooden talempong represent the relationship between humans and nature. The data collection methods used are direct observation, in-depth interviews, documentation and literature studies. This data is then analyzed using the cultural ecology approach by Julian Steward who explains that there is an interaction between culture and the environment that takes place through the adaptation process. The results show that wooden talempong was born from a ritual tradition of gratitude for the people of Nagari Rangking Luluih for the harvest and a good life. Furthermore, the repertoire in the wooden talempong beat tones often describes the harmony of humans and nature. From here it is clearly seen that wooden talempong is not only an art that represents beauty alone. Moreover, in Minangkabau society there is a philosophy of